Study of total phenolic and flavonoid contents, antioxidant, and antibacterial properties of Zanthoxylum chalybeum and Euphorbia ingens: Medicinal plants from Malawi - Kumwenda, F D; Sumani, J; Jere, W; Namandwa, B; Nyirenda, K K; Mwatseteza, J (Plant Science Today, 2025)
This study investigated the chemical composition, antioxidant, and antibacterial activities of two medicinal plants from Malawi: Zanthoxylum chalybeum and Euphorbia ingens. Plant extracts were obtained sequentially macerating the root powder with n-hexane, dichloromethane, ethyl acetate, methanol, and water. Total phenolics and flavonoids were determined by the Folin-Ciocalteau and aluminum chloride methods, respectively, while antioxidant activity was assessed by DPPH and FRAP assays. The antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa was evaluated using the disc diffusion method. Flavonoids ranged from 13.40 to 30.27 mg/g for Z. chalybeum extracts and 21.76 to 66.27 mg/g for E. ingens, with the highest amounts in ethyl acetate extracts of both plants. Both plants had the highest amounts of total phenolics in methanol extracts, with Z. chalybeum and E. ingens exhibiting 284.85 and 351.59 mg/g, respectively. The DPPH radical scavenging activity test showed that E. ingens, with IC50 values of 11.28 and 12.85 ?g/mL for the aqueous and methanol extracts, respectively, is a stronger antioxidant than Z. chalybeum. The FRAP activity was highest in methanol extracts for E. ingens (2831.77±179.02 mg/g) and Z. chalybeum (799.15±32.43 mg/g). Both plants exhibited more potent antibacterial activity against S. aureus compared to P. aeruginosa. Dichloromethane and ethyl acetate extracts of Z. chalybeum showed significant activity against S. aureus with MIC values of 1.56 mg/mL, demonstrating their strong inhibitory potential. The study has revealed that both E. ingens and Z. chalybeum roots would be excellent natural antioxidants and antibacterial agents.